Sustainable Development and Environmental Management Experiences and Case Studies - Clini, Corrado; Musu, Ignazio; Gullino, Maria Lodovica (Springer Netherlands : Imprint: Springer, 2008)
This book presents the new EU approach to environmental management and its attempt to place it in the perspective of sustainable development. China and other large and fast growing economies are putting increasing pressures on global environment, but they are also looking at the European experience with great interest. To present critically this experience can help those countries avoid the mistakes made by developed countries in dealing with the relation between economic growth and environmental protection, and to improve the institutions and tools for better environmental governance. The variety of issues covered and the wide approach used in this book make it a useful tool for readers who want to place themselves in this perspective, although starting from different backgrounds and levels of knowledge on environmental and sustainability sciences.